The Influence of Earning Per Share (EPS), Debt to Equity Ratio (DER) and Price to Earning Ratio (PER) on Stock Prices in Banking Companies Listed on The IDX - Wulandari; Pratiwi, Aliah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to determine the effect of Earning Per Share (EPS), Debt To Equity Ratio (DER) and Price To Earning Ratio (PER) on share prices in banking companies listed on the IDX. . The instrument in this research is to use a table listing the values ??of net profit, total liabilities, total equity, share price and number of outstanding shares from the annual financial reports of 6 banking companies listed on the BEI from 2015-2022. The population in this study is annual financial report data on banking companies registered on the BEI, totaling 47 companies from this population. The research sample is financial reports on banking companies listed on the BEI with the largest asset qualifications in the last 3 years, including Bank BRI. , Bank BNI, Bank BCA, Bank MANDIRI, Bank BTN, Bank CIMB NIAGA from 2015 to 2022. The data collection technique in this research uses documentation and literature study. In this research, the data analysis technique used is the partial least squares (PLS) approach with the SmartPLS version 3.0 software package. The research results show that Earning Per Share and Debt To Equity Ratio do not have a significant effect on share prices in banking companies listed on the IDX. Meanwhile, the Price to Earning Ratio has a significant effect on share prices in banking companies listed on the IDX.